USING TEXT FEATURE WALK TO HELP STUDENTS COMPREHEND EXPOSITORY TEXTS - Jelita Purnamasari; Chuzaimah Dahlan Diem; machdalena Vianty (Faculty of Teacher Training and Education, Universitas Sriwijaya, 2014)
Abstract: In this study, the focus of investigation was on the students’ comprehension on expository text. Specifically, this study was aimed to find out whether or not there was a significant difference in the students’ reading comprehension before and after they were taught by using Text Feature Walks. The population of this study was the eleventh grade students of one of the state senior high schools in Palembang, South Sumatera, Indonesia. The sample was twenty nine students that were taken as the sample by using population-single technique. This study used pre-experimental method, one group pre-test post-test design. The instrument used for collecting the data was a reading comprehension test. The result of the study showed that the use of Text Feature Walks could significantly increase the students’ reading achievement. Key words: reading comprehension, expository texts, Text Feature Walk